PhotonBathymetry: An Interactive Software for Nearshore Bathymetry Using ICESat-2 Data and Multispectral Images - Shuai Xing; Songtao Guo; Guoping Zhang; Xinlei Zhang; Pengcheng Li; Dandi Wang; Li Chen; Ming Gao; Qing Xu (IEEE Access)
In coastal regions, the increasing human activities have made it increasingly important to gain an understanding of the water depths in these areas. Although conducting field measurements for nearshore water depths on a global scale is quite challenging, the fusion of active and passive remote sensing data, utilizing laser altimetry data and multispectral imagery, allows us to obtain valuable nearshore bathymetric information without the need for on-site measurements. In this study, we have developed an interactive software named PhotonBathymetry (PBathy) with the aim of supporting nearshore bathymetry retrieval efforts. The construction of this platform encompasses four key levels: data storage, software workflows, functional plugins, and user services. These levels are designed to ensure the efficiency of data loading, browsing, and processing. To cater to the diverse needs of developers, PBathy is built using C++ and provides standardized interfaces for different programming languages. Furthermore, PBathy has undergone meticulous integration and optimization of its user interface and feature pages to offer an exceptional user experience. To validate PBathy’s capability for nearshore bathymetry retrieval, we conducted a case study on Culebra Island in Puerto Rico. The results demonstrate that PBathy not only successfully performs bathymetric retrieval but also offers additional features such as visual querying of laser altimetry data and multispectral imagery. The introduction of PBathy addresses the limitations of current photon data processing software, providing a viable solution and a solid foundation for nearshore bathymetry retrieval efforts.